COGNITIVE BEHAVIORAL PSYCHOTHERAPY IN THE TREATMENT OF CHRONIC PAIN - K. A. Melkumova (Неврология, нейропсихиатрия, психосоматика)
The use of cognitive behavioral psychotherapy (CBPT) methods in the treatment of patients with chronic pain is considered. Despite the existing difficulties in evaluating the efficiency of CBPT, numerous studies have shown good results when it is used both alone and as part of a multidisciplinary approach. The use of CBPT methods may be considered as an effective non-drug treatment for chronic back pain.